(untitled) (Perner’s Contacts, 2019)
The characteristic feature of rail passenger transport is its high transport capacity. It predetermines the railway to create the key mode of transport. Main bottleneck is the transport infrastructure quality. There are no high-speed rail links in many European Union Member States. The aim of the contribution is to analyse the basic problems of the operation and organization of rail passenger transport and to propose measures for increasing its efficiency, attractiveness, better image in the eyes of the public, but especially the increase of transport performance. By setting the appropriate operational, organizational and infrastructure parameters, the competitiveness of rail transport will be enhanced.